The Development of Mikro Tenis Games for Improving Forehand Technique - Ricko Irawan; Sesaria Nisa Afifi; Tri Nurharsono (International Conference on Science, Education, and Technology, 2021)
The purpose of this study is to develop a tennis game product that can be used to train forehand and baghand strokes by using infrastructure other than tennis courts such as asphalt, paving, and other vacant land. This development research uses a procedural development model, because this model is descriptive, which is a procedure that describes the steps that must be followed in producing a product. In this study, the steps used in developing the tennis microgame model include: (1) conducting product analysis (2) developing an initial product for tennis microgames (3) expert validation (4) field trials (5) product revision. This study used an experimental design as a trial design involving 43 students. The instruments used are interviews, observations, questionnaires and documentation. The data analysis technique uses percentages to assess the feasibility, quality and acceptability of the product. The results of the study: 1) Mikro Tenis games can be used on vacant land, asphalt or pasving, 2) tennis micro games can be used to practice forehand hitting techniques.